A study of comparison of outcomes of positive pressure ventilation and face mask oxygen on arterial blood gas parameters in children with congestive heart failure - Arvind Kumar; Piyali Bhattacharya; Prabudh Paritosh Mishra (Amaltea Medical Publishing House, 2023)
Aims and objective. To compare the effects of Positive Pressure Ventilation (PPV) and Face Mask oxygen on arterial blood gas (ABG) parameters in children with congestive heart failure. Materials and methods. A prospective, randomized, single-blind, cross-sectional study was undertaken in eastern India's Dr. B.C. Roy Post Graduate Institute of Pediatric Sciences PICU. From December 2014 to June 2016, single-blind randomization was used to diagnose congestive heart failure in children aged 3 months to 12 years. Results. Patients receiving face mask oxygen had a mean pH of 7.2150, while those receiving NIV had a mean pH of 7.2740 (P value = 0.012, <0.05). After 6 hours, the pH improved more in the NIV group (mean pH = 7.3023) than the face mask oxygen group (mean pH = 7.2503), P value = 0.003 (<0.05). The group receiving face mask oxygen had a mean pCO2 of 54.93 at the start of the study, while the NIV group had 52.83 (P value = 0.395, >0.05). The baseline pCO2 values of the two groups were similar. After 1-2 hours of investigation, the face mask oxygen group had a mean pCO2 of 53.50, whereas the NIV group had 47.77, with a P value of 0.008 (<0.05). After 4-6 hours, the face mask oxygen group had a mean pCO2 of 50.90, while the NIV group had 46.77, with a P value of 0.001 (<0.05). Conclusion. After 6 hours of therapy, NIV improved mean pH more than face mask oxygen. NIV ventilation improved pCO2 readings more than face mask oxygen after 2 hours. The mean pCO2 drop over 4-6 hours in the NIV group was greater than in the face mask oxygen group.